2022
DOI: 10.3991/ijep.v12i2.29949
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students' Perceptions of the Educational Use of ICTs and Educational Technologies during the Online Learning

Abstract: The impact of the use of ICTs in the university context has been investigated for decades, as they are not only tools in themselves, but also generate a new social space and, therefore, a new educational space known among others as virtual education or online learning (OL). Precisely, OL has been presented as an alternative in the historical context originated by the COVID-19 pandemic, which has created an unexpected situation for social structures and their educational institutions. The main goals of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…The LMS must be able to create an easy-to-use and simplified interface for each participant. Another option also includes the ability to track work performance and generate monthly or annual reports accordingly [25].…”
Section: User Affairs Managementmentioning
confidence: 99%
“…The LMS must be able to create an easy-to-use and simplified interface for each participant. Another option also includes the ability to track work performance and generate monthly or annual reports accordingly [25].…”
Section: User Affairs Managementmentioning
confidence: 99%
“…The methods of earning is one aspect of this coin which needs further investigation but might need to be kept open to teacher discretion as it was found that the role of teachers is an important one when it comes to students adopting a new technology [15]. Furthermore, research from Slovenia found that teachers might have lower confidence but positive attitudes toward technology use in education [16].…”
Section: Overall Interest In Coinmentioning
confidence: 99%
“…Accordingly, adjustable instructions would be proposed to improve students' inadequate skills. So, the impact of using ITS creates instructional interactions between students and teachers as a new social space like other uses of ICTs to construct and support students' perceptions in the educational technologies-based learning environment [20].…”
Section: Features Of Ai-based Instructional Technologymentioning
confidence: 99%